2022
DOI: 10.3389/fmicb.2022.998093
|View full text |Cite
|
Sign up to set email alerts
|

Host transcriptome and microbiome interactions in Holstein cattle under heat stress condition

Abstract: Climate change affects animal physiology. In particular, rising ambient temperatures reduce animal vitality due to heat stress and this can be observed at various levels which included genome, transcriptome, and microbiome. In a previous study, microbiota highly associated with changes in cattle physiology, which included rectal temperature, drooling score and respiratory score, were identified under heat stress conditions. In the present study, genes differentially expressed between individuals were selected … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Luo et al ( 14 ) also discovered seven major candidate genes ( PMAIP1 , SBK1 , TMEM33 , GATB , CHORDC1 , RTN4IP1 and BTBD7 ) associated with physiological indicators of HS (RT, RS and DS) in Holstein cattle by weighted single-step genome-wide analysis studies (WssGWAS). In the transcriptome study by Czech et al ( 106 ), the RAB39B gene was found to be significantly associated with RT, DS and RS under HS conditions in dairy cattle. In addition, Diaz et al ( 107 ) reported five genes: E2F8 , GATAD2B , BHLHE41 , FBXO44 , and RAB39B which were significantly associated with HS in cattle.…”
Section: Genomic Regions and Candidate Genes Associated With Heat Tol...mentioning
confidence: 97%
See 4 more Smart Citations
“…Luo et al ( 14 ) also discovered seven major candidate genes ( PMAIP1 , SBK1 , TMEM33 , GATB , CHORDC1 , RTN4IP1 and BTBD7 ) associated with physiological indicators of HS (RT, RS and DS) in Holstein cattle by weighted single-step genome-wide analysis studies (WssGWAS). In the transcriptome study by Czech et al ( 106 ), the RAB39B gene was found to be significantly associated with RT, DS and RS under HS conditions in dairy cattle. In addition, Diaz et al ( 107 ) reported five genes: E2F8 , GATAD2B , BHLHE41 , FBXO44 , and RAB39B which were significantly associated with HS in cattle.…”
Section: Genomic Regions and Candidate Genes Associated With Heat Tol...mentioning
confidence: 97%
“…The identification of key candidate genes responsible for variation in thermoregulation could inevitably help to improve the efficiency of selective breeding, especially for traits with low heritability in dairy cattle breeding programs. In addition, investigation of the physiological systems regulated by genes involved in thermoregulation is an area that requires further study, as understanding the biological control will aid to prioritize candidate genes for genomic selection strategies (105). A considerable number of GWAS and transcriptome studies have been investigated and identified several candidate causal variants potentially linked with milk production and various physiological indicators of HS in dairy cattle (11, 12, 14, 15, 17-19, 24, 92-94, 96, 106, 107).…”
Section: Genomic Regions and Candidate Genes Associated With Heat Tol...mentioning
confidence: 99%
See 3 more Smart Citations